Ethical decision making in school administration : leadership as moral architecture - Wagner, Paul A., 1947- (SAGE Publications, 2009)
Pedagogically rich, demographically inclusive, and culturally sensitive, Ethical decision making in school and district administration exposes educational leaders to an interdisciplinary array of theories from the fields of education, economics, management, and moral philosophy (past and present). Authors Paul A. Wagner and Douglas J. Simpson demonstrate how understanding key concepts can dramatically improve management styles and protocols. Key features contains numerous case studies that apply the book's concepts to relevant ethical issues faced by school administrators.